Pengaruh Karakteristik Individu, Iklim Organisasi Dan Beban Kerja Terhadap Kinerja Karyawan (Studi Pada PT. Bank Negara Indonesia (Persero) Tbk. Kantor Cabang Tasikmalaya) - Annisa Desty Puspatriani (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
The purpose of this study was to find out and analyze the effect of individual characteristics, organizational climate and workload on employee performance at PT. Bank Negara Indonesia (Persero) Tbk. Tasikmalaya Branch Office. The research method used in this research is descriptive analysis method, using census techniques. Data collection techniques using documentation study methods and field research (field research) which includes observation, interviews and questionnaires. The population in this study are employees at PT. Bank Negara Indonesia (Persero) Tbk. Tasikmalaya Branch Office, with a total of 113 respondents. The analysis technique used in this research is path analysis. By using path analysis, researchers suggest that partially, individual characteristics, organizational climate and workload have a significant positive effect on employee performance. Simultaneously, individual characteristics, organizational climate and workload have a significant effect on employee performance. Thus, the better the individual characteristics, organizational climate and workload, the employee's performance will increase.